PENGARUH EFEKTIVITAS SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA KARYAWAN DENGAN PEMANFAATAN TEKNOLOGI INFORMASI SEBAGAI VARIABEL MODERASI (Studi pada Bank-Bank di Kota Bengkulu) - Lismawati, Lismawati (Jurnal Akuntansi dan Bisnis, 2022)
This study aims to examine and analyze the effect of the effectiveness of accounting information systems on employee performance and to prove how the use of information technology moderates the effect of accounting information systems on employee performance. The population of this study were all employees of the finance department at conventional banks in Bengkulu City. Determination of the sample is done by purposive sampling method. The results show that the effectiveness of accounting information systems has a positive effect on employee performance and the use of the effectiveness accounting information technology does not moderate the effect of accounting information systems on employee performance. The theoretical implications of the results of this study are support the goal setting theory which In this case the existence of an accounting information system will lead to behavioral patterns for employees to work more optimally in a company so that it will improve employee performance and company goals will be achieved and practically, the results of this study are expected to be input for several banks in Bengkulu City to understand how the influence of accounting information systems on employee performance.  Keywords:   Effectiveness of Accounting Information System, Employee Performance, Utilization of Information Technology, Bank